Community service through toddlers’ mentoring Posyandu in Cihanjuang Village - Vania Nurshavira; Renaldi Malik; Sjaeful Anwar (Universitas Pendidikan Indonesia, 2024)
The successful implementation of the community health development program to improve the quality of public health in Cihanjuang Village cannot be separated from the support and various active roles of the entire community from various circles. The role of Posyandu is in improving the quality of maternal and child health and Posyandu is a community health center. Posyandu plays an important role in improving the quality of maternal and child health through health service processes such as family planning, nutrition, vaccination, and MCH services. This Kuliah Kerja Nyata activity aims to provide education regarding the importance of monitoring maternal and child health at posyandu. Data collection was obtained through interviews and observations. The results obtained show that mothers in Cihanjuang Village already understand the importance of vaccination status and children's health, but need to receive training to determine children's nutritional status and know the appropriate vaccination intervals. This counseling activity is expected to be carried out regularly every month to detect any deviations in growth and take corrective action as soon as possible so as not to disrupt the child's growth and development process. Abstrak Keberhasilan pelaksanaan program pembangunan kesehatan masyarakat untuk meningkatkan mutu kesehatan masyarakat di Desa Cihanjuang tidak lepas dari dukungan dan berbagai peran aktif seluruh masyarakat dari berbagai kalangan. Peran Posyandu dalam meningkatkan kualitas kesehatan ibu dan anak dan Posyandu merupakan pusat kesehatan masyarakat. Posyandu berperan penting dalam meningkatkan kualitas kesehatan ibu dan anak melalui proses pelayanan kesehatan seperti KB, gizi, vaksinasi, dan pelayanan KIA. Kegiatan Kuliah Kerja Nyata ini bertujuan untuk menyelenggarakan penyuluhan mengenai pentingnya pemantauan kesehatan ibu dan anak di posyandu. Pengumpulan data diperoleh melalui wawancara dan observasi. Hasil yang diperoleh menunjukkan bahwa para ibu di Desa Cihanjuang sudah memahami tentang pentingnya status vaksinasi dan kesehatan anak, hanya saja perlu mendapatkan pelatihan untuk menentukan status gizi anak dan mengetahui interval vaksinasi yang sesuai. Kegiatan penyuluhan ini diharapkan dilakukan secara rutin setiap bulannya untuk mendeteksi adanya penyimpangan pertumbuhan dan mengambil tindakan perbaikan sesegera mungkin agar tidak mengganggu proses tumbuh kembang anak. Kata Kunci: kesehatan ibu dan anak; kuliah kerja nyata; pemantauan pertumbuhan balita; posyandu